2002
DOI: 10.1097/00129689-200210000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Devine Exclusion Gastroenterostomy for the Palliation of Unresectable and Obstructing Gastric Carcinoma

Abstract: The Devine exclusion gastroenterostomy is an effective procedure for the relief of gastric outlet obstruction in patients with unresectable carcinoma of the gastric antrum. We report on the successful laparoscopic application of this technique in two male patients aged 61 and 76 years with unresectable and obstructing antral gastric cancer. The operating time was 90 minutes for each patient, and the postoperative hospital stay was 3 and 4 days, respectively. There were no delays in gastric emptying and no recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…The GJ was fashioned using either a hand‐sutured two‐layer technique or a combination of staples and sutures. The operative techniques of laparoscopic loop, Roux‐en‐Y, and exclusion gastric bypass have been described preciously …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GJ was fashioned using either a hand‐sutured two‐layer technique or a combination of staples and sutures. The operative techniques of laparoscopic loop, Roux‐en‐Y, and exclusion gastric bypass have been described preciously …”
Section: Methodsmentioning
confidence: 99%
“…The operative techniques of laparoscopic loop, Roux-en-Y, and exclusion gastric bypass have been described preciously. [9][10][11][12]…”
Section: Operative Techniquesmentioning
confidence: 99%
“…8-10 Laparoscopic Devine's procedure for the palliation of GOO has also been reported. [11][12][13] Therefore, considering the benefits of laparoscopic approach as a minimally invasive surgery, we also performed LMDVSR recently.…”
Section: Discussionmentioning
confidence: 99%
“…11 Ammori's procedure is an antecolic loop gastrojejunostomy performed after transection of the stomach 5 cm proximal to the obstructing antral tumor with the use of a stapler, and Braun's anastomosis is not performed. 12 Suzuki's procedure is an antecolic side-toside Roux-en-Y gastrojejunostomy after hemitransection (a 3-cm-wide segment near the lesser curvature is not transected), with side-to-side jejunojejunostomy. 13 However, transection of the stomach may prevent postoperative DRGE and hemorrhage of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Choi 11 reported that laparoscopic gastrojejunostomy also causes less suppression of immune function than open gastrojejunostomy. Other authors have previously reported, as a minimally invasive approach, laparoscopic Devine exclusion gastrojejunostomy for palliation of gastric outlet obstruction in antral gastric cancer 13 and for secondary to recurrent cholangiocarcinoma. 14 However, we consider that when using the Devine procedure it is not possible to observe antral tumors owing to the complete transection of the stomach.…”
Section: Discussionmentioning
confidence: 99%